2006
DOI: 10.1200/jco.2006.24.18_suppl.18628
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates and oral cavity avascular bone necrosis: A review of 12 cases

Abstract: 18628 Background: Intravenous bisphosphonates are the current standard of care for the treatment of hypercalcemia of malignancy and for the prevention of skeletal complications associated with bone metastases. Generally, the i.v. administration of bisphosphonates is well tolerated. Recently, retrospective case studies have reported an association between long-term bisphosphonate therapy and osteonecrosis of the jaws. Methods: We reviewed data for 12 patients referred to either an oral and maxillofacial surgeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…However, increasing numbers of cases report adverse side effects of long-term bisphosphonate therapy, which are found in the form of jaw osteonecrosis particularly in those who received high-dose intravenous bisphosphonate therapy (43). Localized vascular insufficiency in the bone is implicated in the pathogenesis of this osteonecrotic process, causing an initial micro-damage that leads to a loss in some mass of the bone, or even results in bone fracture (109). To reduce such side effects by bisphosphonates, attempts have been made to enhance the bioavailability of bisphosphonates by utilizing administration routes other than intravenous injection, such as nasal administration, subcutaneous and intramuscular injections, implants and targeted osteotropic delivery systems (42).…”
Section: Anti-rankl Antibodymentioning
confidence: 99%
“…However, increasing numbers of cases report adverse side effects of long-term bisphosphonate therapy, which are found in the form of jaw osteonecrosis particularly in those who received high-dose intravenous bisphosphonate therapy (43). Localized vascular insufficiency in the bone is implicated in the pathogenesis of this osteonecrotic process, causing an initial micro-damage that leads to a loss in some mass of the bone, or even results in bone fracture (109). To reduce such side effects by bisphosphonates, attempts have been made to enhance the bioavailability of bisphosphonates by utilizing administration routes other than intravenous injection, such as nasal administration, subcutaneous and intramuscular injections, implants and targeted osteotropic delivery systems (42).…”
Section: Anti-rankl Antibodymentioning
confidence: 99%
“…[ 3 ] But, with lower dose of oral bisphosphonate, BRONJ cases were also reported sporadically. [ 1 , 15 , 16 ] Association of Oral and Maxillofacial Surgeons reported local risk factor of BRONJ as 1) Extractions, 2) Dental implant placement, 3) Periapical surgery, 4) Periodontal surgery involving osseous injury and suggest three months of drug discontinuation prior to elective dental invasive procedure reduces the risk of developing BRONJ. [ 3 ] A common pathogenesis of BRONJ and AFF explains that the Jaw bone and lateral cortex of subtrochanteric area of femur demand to endure higher mechanical stress than the other bones that are comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it will inhibit the production of farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate (GGPP), so that some small GTPases cannot be synthesized efficiently, leading to the apoptosis of osteoclasts . NG, a polymethoxylated flavonoid, has been reported to promote bone formation by stimulating the proliferation of mesenchymal stem cells (MSCs) and the differentiation of osteoblasts, depending on the high expression of some osteogenesis-related genes, such as bone morphogenetic protein-2 (BMP-2). , For the small molecules, they have some advantages toward the growth factors, including low toxicity, low cost, and low risk of immune response. Meanwhile, many studies have demonstrated that sustained release of these small molecules in situ can be more effective than long-term systemic treatment and will not lead to some side effects, such as osteoclast dysfunction and osteonecrosis. , …”
Section: Introductionmentioning
confidence: 99%
“…22−24 Meanwhile, many studies have demonstrated that sustained release of these small molecules in situ can be more effective than long-term systemic treatment and will not lead to some side effects, such as osteoclast dysfunction and osteonecrosis. 25,26 Although the local use of each molecule has been shown to have a positive effect on osteogenesis, there have been no reports of combining them for promoting bone regeneration. The imbalance between the anabolic activities of osteoblasts and the catabolic activities of osteoclasts during bone healing can result in abnormal physiological conditions, such as osteoporosis, hyperostosis, Paget's disease, and rheumatoid arthritis.…”
Section: ■ Introductionmentioning
confidence: 99%